ADIKSI PENGGUNAAN SMARTPHONE DENGAN KETERAMPILAN KOMUNIKASI INTERPERSONAL SISWA/I SMAN 8 KOTA BATAM - Ariani, Fitria; Nurul Aulia, Devy Lestari (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
The human needed to always communicate with others and their environment brings them to grow the technology, to improve the device that can keep the relationship. One of that device called as smartphone. Smartphone is then dominated the people’s life individually, and further the people from their environment. This research aims to investigate the correlation of the addiction of smartphone use and interpersonal communication skill. This research employs the quantitative method by cross-sectonal approach. The research was conducted from may to june 2017. The population is student of SMA 8 Batam. The data collecting technique employs non random sampling (non probability) with purposive sampling technique. Statistically, the chi-square test reveals p value = 1,000 (p value > 0,05) indicating the significant correlation of the addiction of smartphone use and interpersonal communication skill. In conclusion, there is no correlation between the use of smartphone and interpersonal communication skill in SMA 8 Batam 2017. In suggestion, the students are expected to be wise controlling the time of smartphone use and improve their interpersonal communication skill.